Priorities of impact investing in environmental protection projects: the case of the future post-war reconstruction of Ukraine - Rieznyk, Oleksandra; Treus, Alla; Kozmenko, Serhiy (Business: Theory and Practice, 2023)
The purpose of this article is to identify environmental protection projects for priority impact investing on the example of the future post-war reconstruction of Ukraine. To evaluate priorities, it is proposed to use the results of a survey of ten independent experts in the field of environmental projects and ecology, belonging to the public, private and non-profit sectors of Ukraine. The survey includes an assessment of environmental protection projects based on the importance and effectiveness of their impact, the characteristics of stakeholders, the duration and risks of the projects, their contribution to the environment and sustainable development. The obtained scores are ranked based on the criteria of Laplace, Wald, Hurwitz, Savage, and Bord and Condorcet rules. In accordance with this, the most priority projects for impact investing are environmental protection projects aimed at land reclamation, conservation and protection, forest restoration, implementation of the national system of trading quotas for greenhouse gas emissions, and eco-modernization of industrial and infrastructural enterprises. This indicates the need for a comprehensive multi-vector approach to the selection of priority areas for impact investing. The lessons learned will be useful for the effective direction or selection of investment projects, their forecasting and analysis.